2023
DOI: 10.1111/jgs.18495
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the pragmatic characteristics of advance care planning outcome measures in dementia clinical trials: A scoping review

Jennifer L. Gabbard,
Joan G. Carpenter,
Natalie C. Ernecoff
et al.

Abstract: BackgroundAdvance care planning (ACP) is a process that involves discussing a person's goals, values, and preferences; it is particularly important for persons living with dementia (PLWD) given that dementia is incurable and progressive. To ensure results that will impact real‐world practices, ACP outcome measures must be psychometrically strong, meaningful to key partners, and pragmatic to collect. Therefore, we conducted a scoping review of outcome measures utilized in ACP randomized controlled clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Future studies should consider appropriate sampling techniques like stratified randomization to ensure participation reflective of the larger population. Lastly, further studies should investigate the long-term impacts of the Koda platform on measures of patient and caregiver experience and goal-concordant care [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should consider appropriate sampling techniques like stratified randomization to ensure participation reflective of the larger population. Lastly, further studies should investigate the long-term impacts of the Koda platform on measures of patient and caregiver experience and goal-concordant care [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…As ADRD‐embedded pragmatic clinical trials are designed and implemented, the IMPACT PCRO Core will review the outcomes they use. Our adapted PAPERS approach will permit evaluation of the pragmatic characteristics of clinical trial outcomes, as demonstrated in a recent review of ADRD advance care planning interventions 25 . These trends will expand the range of outcomes used in embedded ADRD pragmatic clinical trials.…”
Section: Discussionmentioning
confidence: 99%